Analisis Fenomena Tindak Pidana Penimbunan Alat Medis di Masa Pandemi COVID-19 Perspektif Hukum Islam - Anggifatul Hana; Nickmetin Erbakan Zen; Regina Masli (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This  research  aims  to  analyze  the  phenomenon  of  hoarding  masks  and  hand  sanitizers  during  the  COVID-19  pandemic  based  on  the  Law  of  the  Republic  of  Indonesia  Number  7  of  2014  and  Presidential  Regulation  of  the  Republic  of  Indonesia  Number  71  of  2015.  Islam  also  prohibits  the  hoarding  of  all  types  of  goods  that  people  need  or  that  can  referred  to  as  "ihtikar".  This  research  shows  that  ihtikar  has  violated  the  concept  of  Maqashid  Ash  Shari'ah,  namely  the  protection  of  religion  (hifdz  al-Din),  protection  of  life  (hifdz  al  Nafs),  and  protection  of  property  (hifdz  al-Mal).  Therefore,  the  existence  of  statutory  regulations  aims  to  prevent  the  occurrence  of  criminal  acts  of  hoarding  (ihtikar),  so  that  Maqashid  Ash  Shari'ah  can  be  realized  and  can  improve  the  prosperity  of  people's  daily  lives.  Hopefully,  the  results  of  this  research  can  become  a  reference  and  be  useful  for  anyone  who  wants  to  seek  justice  in  handling  hoarding  cases  as  discussed  in  this  research.